2019
DOI: 10.1159/000502978
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Enables Chronic Corticosterone to Inhibit Pulsatile Luteinizing Hormone Secretion and Suppress Kiss1 Neuronal Activation in Female Mice

Abstract: Introduction: Two common responses to stress include elevated circulating glucocorticoids and impaired luteinizing hormone (LH) secretion. We have previously shown that a chronic stress level of corticosterone can impair ovarian cyclicity in intact mice by preventing follicular-phase endocrine events. Objective: This study is aimed at investigating if corticosterone can disrupt LH pulses and whether estradiol is necessary for this inhibition. Methods: Our approach was to measure LH pulses prior to and followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 57 publications
(70 reference statements)
2
42
0
Order By: Relevance
“…The model reproduced the effects of ovarian hormone removal (OVX) and restitution (E 2 ) on the HPA and HPG axes dynamics, both under physiological conditions [12] (Fig. 3) and under exogenous CORT excess [8] (Fig. 4).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The model reproduced the effects of ovarian hormone removal (OVX) and restitution (E 2 ) on the HPA and HPG axes dynamics, both under physiological conditions [12] (Fig. 3) and under exogenous CORT excess [8] (Fig. 4).…”
Section: Discussionmentioning
confidence: 83%
“…In a recent study, Kreisman and co-workers [8] investigated the effect of chronic CORT administration on LH pulsatility and demonstrated the importance of gonadal steroid hormones in mediating the inhibitory effect of CORT on the HPG axis. The study showed that a pellet delivering a high dose of CORT over 48 hrs in OVX mice has no effect on LH pulsatility, whereas a significant reduction of LH pulse frequency is observed in OVX animals treated with a 17β-estradiol silastic implant (OVX+E 2 ).…”
Section: Estradiol-mediated Inhibition Of Hpg Dynamics By High Cort Dmentioning
confidence: 99%
See 3 more Smart Citations